Chemically treated plastic replacing fine aggregate in structural concrete - El-Nadoury, Wegdan W. (Frontiers in Materials, 2022)
Plastic wastes (PW) create chronic environmental problems mainly because it is not biodegradable. The utilization of PW as a fractional substitution of fine aggregate in concrete production is a sustainable application. However, the smooth surface of plastic weakens the cement-plastic bond and consequently lessens the mechanical properties of concrete. This research improves the cement-plastic bond by increasing the hydrophilicity and coarseness of polyethylene terephthalate (PET) through chemical treatment with 5wt% polystyrene (P.S.) and 5wt% PKHH-phenoxy resin. Twenty eight mixtures with different w/c ratio; 0.4, 0.45, 0.5, and 0.6 and different percentage of sand substitution; 5%, 20%, and 50% are cast. Tests are conducted to determine the behavior of fresh and hardened concrete in terms of workability, water absorption, density, compressive strength, flexural strength, splitting tensile strength, and durability. Results show that the proposed chemical treatment rises the cement-plastic bond. The compressive, splitting tensile, and flexural strength were improved by 45%, 35%, and 6% respectively compared to corresponding untreated plastic recycled concrete. The highest mechanical properties are achieved for mixes with 5% plastic. Nevertheless, a 20% replacement of sand with treated plastic can be used effectively to produce structural concrete.